Modeling and simulation of computer networks and systems methodologies and applications - Mohammad S. Obaidat; Zarai, Faouz; Nicopolitidis, Petros (Morgan Kaufmann, 2015)
Modeling and Simulation of Computer Networks and Systems: Methodologies and Applications introduces you to a broad array of modeling and simulation issues related to computer networks and systems. It focuses on the theories, tools, applications and uses of modeling and simulation in order to effectively optimize networks. It describes methodologies for modeling and simulation of new generations of wireless and mobiles networks and cloud and grid computing systems